The Optimization the use of Amylum Manihot in Paracetamol Tablet Formulation Using Wet Granulation Method (Journal of Science and Technology Research for Pharmacy, 2022)
The oral route of drug administration is preferred by most of the patients. One of the most preferred oral preparations are tablets. Tablets are solid dosage forms containing active ingredients with or without fillers. One of the additions to the manufacture of tablets is a binder. The manufacture of tablets depends on the nature of the active substance used. Paracetamol is an active substance that has poor flow properties and compressibility, so it requires a binder and a wet granulation method for making tablets in order to increase fluidity and good compressibility. Amylum manihot is one of the starches used as additives in the pharmaceutical industry. This starch is very suitable to be used as a binder in the manufacture of tablets by the wet granulation method. In this review article, we will discuss the general method of making tablets, namely the wet granulation method using amylum manihot as a bonding agent and the evaluation of granules and tablets, namely the flow time test, angle of repose test, determination test, weight uniformity test.